CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN PT INDONESIA POWER UJP PLTU JERANJANG DALAM MENGURANGI KEMISKINAN (Studi kasus pada masyarakat Desa Taman Ayu Kecamatan Gerung Kabupaten Lombok Barat) - Banyu Arma supija; Lalu Ahmad Rahmat; Yulanda Trisula Sidharta Yohanes (Universitas Mataram, 2018)
Creating a positive image in society, companies can conduct CSR programs. Poverty categories are understood in various ways including: Picture of material shortage, Overview of social needs, Descriptions of lack of income and adequate wealth. The meaning of